Analysis and modeling of crustal deformation using InSAR time series along selected active faults within the Africa-Eurasia convergence zone - (:unkn) unknown (My University, 2015)
This Ph.D. thesis is conducted in the frame of the -co-tutellell scholarship (EOST-ITU) provided by French Embassy in Ankara. ln addition, a 10-month scholarship « Bourse excellence Eiffel » ,and 8-month scholarship « TUBITAK 22148 - joint Ph.D. » were other sources of support for the preparation of this thesis.The convergence between African and Eurasian plates is at the origin of active tectonic structures that generate large and destructive earthquakes. This thesis aims to improve our understanding of fault behavior and the earthquake cycle by analyzing surface deformation along selected active faults during the periods of co-, post-and inter-seismic deformation within the Africa-Eurasia convergence zone. ln this context, slow deformation observed at the surface and associated with the earthquake cycle is analyzed using Synthetic Aperture Radar lnterferometry (lnSAR) time series technique, and modeled with elastic dislocation methods.
Keywords: African Research